Bread, Cement, Cactus A Memoir of Belonging and Dislocation - Zaidi, Annie (Social Sciences, 2020)
In this prize-winning exploration of the meaning of home, Annie Zaidi reflects on the cultural conflicts in India that have shaped her identity. Zaidi provides a nuanced perspective on land and regional affinity, migration and otherisation, and the ways in which memory works to attach us to a particular place.